Unsaturated nitrogen-rich polymer poly(l-histidine) gated reversibly switchable mesoporous silica nanoparticles using "graft to" strategy for drug controlled release. (November 2017) - Mu, Shengjun; Liu, Yongjun; Wang, Tianqi; Zhang, Jing; Jiang, Dandan; Yu, Xiaoyue; Zhang, Na
Graphical abstract: Abstract: A novel and intelligent pH-controlled system having an "on-off" switch based on poly(l -histidine) (PLH) and poly(ethylene glycol) (PEG) coated mesoporous silica nanoparticles (MSNs) (MSNs-PLH-PEG) was designed and evaluated for tumor specific drug release. The unsaturated nitrogen-rich polymer, PLH, which can change its solubility at different pH values, was employed for establishing the reversible "on-off" switch. In vitro drug release results demonstrated that MSNs-PLH-PEG has a pH-controlled "on-off" profile with the change of pH value between pH 7.4 and 5.0. Furthermore, in vitro cellular uptake study results showed that the entrapped drug could be efficiently released from MSNs-PLH-PEG under acidic endosome/lysosome. In vitro cell cytotoxicity and in vivo antitumor studies results indicated that sorafenib loaded MSNs-PLH-PEG exhibited good anti-proliferation and tumor growth inhibition effects. Haemolysis assay and histological analysis of MSNs-PLH-PEG showed negligible haemolysis activity and no visible tissue toxicity at the test dose. This study represents a promising and intelligent pH-controlled intelligent system for drug delivery and controlled release. Statement of Significance: A novel pH-controlled intelligent and reversible "on-off" switch system based on poly(l -histidine) and poly(ethylene glycol) coated mesoporous silica nanoparticles (MSNs-PLH-PEG) by "graft to" synthesis method was constructed for tumor specific drug release. The unsaturated nitrogen-rich pH-sensitive polymer, PLH, which can change its solubility in different pH values, was employed as the reversible "on-off" switch in MSNs for the first time. The pH-controlled "on-off" switch manner was observed in the drug release results in vitro . In the in vivo antitumor studies, sorafenib loaded MSNs-PLH-PEG could effectively suppressed tumor growth in H22 tumor bearing mice. It is expected that the pH-controlled intelligent "on-off" switch system we designed holds remarkable promise and provides valuable strategy for possible applications in cancer therapy.